Evaluating contamination levels in fresh foods markets and assessing the likelihood of implementing food safety programs in Paraguay - Mendez Sosa, Ellen Andrea (Kansas State University, 2024)
Paraguay is a country located in the southern cone region of the Americas; its population reaches over 7 million people, of which 26.4% lies under the poverty line and 11% is considered undernourished. Paraguay is a highly agricultural country; however, most of the food produced is destined for exportation. Paraguay sits among the top exporters of soybean and beef, and exports most of the corn and wheat produced in the country. Most of the domestically produced food that is destined for local consumption is produced by the denominated family agriculture or family farming which are small-scale farms operated mainly by family members and considered a rural productive activity. Vegetable producers are not required to have a food safety plan; however, they must follow Good Agriculture Practices (GAP) to produce vegetables products. Moreover, meat processors are required to implement Hazard Analysis and Critical Control Points (HACCP), but only for meat products that are intended for export. Family farmers commonly distribute their products in fresh foods markets where other traders, distributors, and intermediaries also commercialize different products. Among the foods sold within these markets are vegetables that are typically consumed raw (e.g., lettuce, tomato, herbs, cucumber); therefore, it is critical that these markets maintain hygienic conditions and implement practices that reduce the likelihood of microbial contamination of the products sold. To adequately develop and assess the efficacy of strategies that address food safety in fresh food markets, it is important to collect baseline data regarding contamination levels and types of microorganisms present in the foods sold within the markets and the market environment itself. Implementing food safety management systems (FSMS) in any stage of the food production chain can reduce the likelihood of contamination. HACCP is a process-based FSMS that is effective in preventing, reducing or eliminating hazards from food products. In addition to having a FSMS, there is a need to have a system that addresses cultural factors and the way people behave around food safety: a behavior-based food safety system. The likelihood a practitioner performs the necessary behaviors to effectively implement a HACCP system can be a function of the practitioners own perceptions as to their capabilities, opportunities, and motivations to perform said behaviors. By evaluating and identifying factors that influence capabilities, opportunities, and motivations necessary to implement a HACCP system, it is possible to design education or engagement programs that increase the likelihood of implementing HACCP as a system in different Paraguayan food commodities and products. Toward this goal, the first part of this dissertation describes a study aimed at establishing a baseline for microbial contamination in both vegetables (i.e., lettuce and tomato) and the market environment (i.e., food contact [FC] and non-food contact [NFC] surfaces) by enumerating indicator microorganisms and detecting pathogenic bacteria. The second part of the dissertation describes a study that uses behavior theory to understand the likelihood that public sector practitioners implement HACCP programs within food processing facilities of Paraguay. A total of 750 samples were collected from fresh food markets (275 FC, 274 NFC, 97 lettuces, and 104 tomatoes) for microbial analysis. Enumeration data of indicator microorganisms (i.e., aerobic counts, Enterobacteria, total coliforms, and generic Escherichia coli) were measured for each sample as well as the presence of Salmonella enterica and Listeria monocytogenes. Enterobacteria showed high levels of contamination in all sample types with lettuce samples presenting the highest average (5.01 log CFU/g, Confidence Interval [CI]: 4.56, 5.46 log CFU/g), and NFC the lowest average (0.29 log CFU/cm², CI: -0.08, 0.66 log CFU/cm²). Results for generic E. coli showed levels below 2.5 log CFU/g or cm² for all sample types. Regarding pathogenic bacteria, presumptive positive results for Salmonella were observed in 13% of NFC surfaces, 42% of FC surfaces, 49% of tomato, and 54% of lettuce samples; while for L. monocytogenes, presumptive positive results were obtained from 51% of NFC surfaces, 50% of FC surfaces, 29% of tomato, and 43% of lettuce samples. Nevertheless, surprisingly, no presumptive samples were confirmed as positive through PCR analysis for either pathogen. These results suggest that both vegetables and the environments within these markets contain high levels of microbial contamination. Levels observed in the environment are especially problematic for cross-contamination and may increase the likelihood of contaminated final products. In the second study, a validated survey instrument was used to measure the perception of capability, opportunity, and motivation to implement HACCP as perceived by personnel from food-regulating bodies from the public sector who have an active role in the implementation of food safety programs within the food industry in Paraguay. A total of 38 responses were collected from both male (N=19) and female (N=19) participants who had (N=23) or did not have (N=15) a HACCP certification. Overall, participants’ perceived opportunity to implement HACCP was lower (p < 0.0001) than participants’ perceived capability or motivation to implement HACCP. Additionally, female participants showed a lower perceived capability to implement HACCP as compared to male participants (p < 0.0001). Analysis showed no statistical difference (p > 0.05), between male and female participants’ overall perceived capabilities to implement HACCP; while perceived motivation was higher among male participants compared to female participants (p < 0.0001). Furthermore, having a HACCP certification increased male perceived capability (p < 0.05) and female perceived motivation (p < 0.05) to implement HACCP, although it did not significantly affect the perceived opportunity between male and female participants (p > 0.05). These data indicate that participants, particularly females, have lower perceived opportunity to implement HACCP, which could decrease the overall likelihood of implementing HACCP systems. Nonetheless, education or engagement programs aimed at increasing perceived opportunity of members from food regulatory bodies could be effective in increasing the likelihood of implementing a HACCP system. In summary, this dissertation shows that there is a need to address hygiene and sanitary conditions in fresh food markets in Paraguay to reduce risk of microbial contamination of the products being sold. Moreover, it is critical to improve opportunities for Paraguayan food-regulating public sector personnel—particularly women—that can lead to an increased likelihood of implementing HACCP as a system in the food industry.
Keywords: Food safety; Paraguay; HACCP system; Contamination